“He Never Wants to Leave. I Would Leave in a Second.” Examining Perceptions of Rural Life and its Impact on Families who Migrate for Employment and Those who Stay Behind in Atlantic Canadian Communities - Murray, Christina; Skelding, Hannah S.; Lionais, Doug (Frontiers in Sociology, 2021)
In Canada, interprovincial labor migration is a common form of mobile work that is significant for rural communities especially in Atlantic Canada. Unique to this form of labor migration is the gendered nature of the phenomenon resulting in men often leaving their wives, families and rural communities behind for employment opportunities in the oil and gas sectors thousands of kilometers away. As men leave their families and communities for employment, women who are left behind become primary caregivers to children in addition to also being the primary caretakers of the family home. The Tale of Two Islands project was a multi-year, cross regional mixed methods research study that examined labor mobility and its impact on families and communities. This paper examines how labor migration has impacted families and rural communities. Drawing upon focus group, conversational and key informant interviews with families impacted by mobile labor and practitioners who serve them, societal perceptions of gendered norms and perceptions of rural life became illuminated. This has contributed to multiple contradictions and role confusion as families adapt and adjust to periods of reunification and separation while striving to remain connected to their rural communities. Men yearn for opportunities to be an active member of their home communities but cannot a result of living away for extended periods of time. In contrast, women who stay behind in rural communities often chose to isolate from community activities as a result of perceived judgments that are attributed to traditional views of rural life and family roles.